Sedation in gastrointestinal endoscopy: a prospective study comparing nonanesthesiologist-administered propofol and monitored anesthesia care - de Paulo, Gustavo Andrade; Martins, Fernanda P.B.; Macedo, Erika P.; Gonçalves, Manoel Ernesto P.; Mourão, Carlos Alberto; Ferrari, Angelo P. (Endoscopy International Open, 2015)
Introduction: Adequate sedation is one of the cornerstones of good quality gastrointestinal endoscopy (GIE). Propofol sedation has increased significantly but there has been much debate over whether it can be administered by endoscopists. The aim of this prospective trial was to compare nonanesthesiologist-administered propofol (NAAP) and monitored anesthesia care (MAC). Methods: A total of 2000 outpatients undergoing GIE at Hospital Albert Einstein (São Paulo, Brazil), a tertiary-care private hospital, were divided into two matched groups: NAAP (n = 1000) and MAC (n = 1000). In NAAP, propofol doses were determined by the endoscopist. A second physician stayed in the room during the entire procedure, according to local regulations. In MAC, the anesthesiologist administered propofol. Results: In total, 1427 patients (71.3 %) were ASA (American Society of Anesthesiologists) class I and 573 were ASA class II. In NAAP, patients received more propofol + fentanyl (61.1 % vs. 50.5 %; P < 0.05) and there were fewer cases of deep sedation (44.7 % vs. 66.1 %; P < 0.05). Hypoxemia rates were similar (12.8 % for NAAP and 11.2 % for MAC; P = 0.3) but these reverted more rapidly in MAC (4.22 seconds vs. 7.26 seconds; P < 0.05). Agitation was more frequent in MAC (14.0 % vs. 5.6 %; P < 0.05). No later complications were observed. Patient satisfaction was very high and similar in both groups. Conclusion: In this setting, NAAP was as safe and effective as MAC for healthy patients undergoing GIE.Clinical trial ref. no.: U1111-1134-4430